1
$\begingroup$

I apologize if this question already exists, but it was quite difficult to word.

In my math class today, we learned how to factor a difference of two perfect cubes. One of our practice questions was:

factor $x^6 - 64$

almost everyone other than me (including my teacher, as he was rushing) ended up with:

$(x^2 - 4)(x^4 + 4x^2 + 16)$

I pointed out two things:

1:

$(x^6 - 64)$ was also a difference of two perfect squares, and we could factor it into this:

$(x^3 + 8)(x^3 - 8)$

Which could then be factored further into:

$(x + 2)(x^2 - 2x + 4)(x - 2)(x^2 + 2x + 4)$

and 2:

the $(x^2 - 4)$ was also a difference of two perfect squares, and we could factor further:

$(x + 2)(x - 2)(x^4 + 4x^2 + 16)$

Now for my question:

How are $(x + 2)(x^2 - 2x + 4)(x - 2)(x^2 + 2x + 4)$ and $(x + 2)(x - 2)(x^4 + 4x^2 + 16)$ equivalent?

The teacher didn't seem to know off the top of his head, and I can't figure it out after trying for a half an hour. I've heard that you can factor the sum of two perfect squares with imaginary numbers, so maybe i can do something there to help explain this?

edit: fixed instances of "- 16" to "+ 16", and "4x" to "4x^2" (thanks for pointing that out)

$\endgroup$
  • 1
    $\begingroup$ It should read $x^6-64=(x^2-4)(x^4+4x^2+16)$. And $$x^4+4x^2+16=(x^4+8x^2+16)-4x^2=(x^2+4)^2-(2x)^2...$$ Yes, it is very likely that something similar has been handled earlier. $\endgroup$ – Jyrki Lahtonen Nov 16 '16 at 16:45
  • $\begingroup$ @Arthur, the quartic is actually $x^4+4x^2+16$, not $x^4+4x+16$. I.e., there were two errors, not just one. $\endgroup$ – Barry Cipra Nov 16 '16 at 18:08
  • $\begingroup$ $(x^2 - 2x + 4)(x^2 + 2x + 4) = x^4 + 4x^2 + 16$ so ... why not? $\endgroup$ – fleablood Nov 16 '16 at 21:36
4
$\begingroup$

It's a very common mistake (*) to think that, since $t^2+4t+16$ is irreducible over the reals, also the polynomial obtained with $t=x^2$ is irreducible.

Over the reals, every polynomial of degree $>2$ is reducible, so also $x^4+4x^2+16$ is reducible.

The trick here is to push in a difference of squares: if you add and subtract $4x^2$, you get $$ x^4+8x^2+16-4x^2=(x^2+4)^2-(2x)^2=(x^2+4-2x)(x^2+4+2x) $$ so you get the same factorization as with the other method.

Another funny example is $x^4+1$: $$ x^4+1=x^4+2x^2+1-2x^2= (x^2+1)^2-(\sqrt{2}\,x)^2= (x^2+1-\sqrt{2}\,x)(x^2+1+\sqrt{2}\,x) $$ which is the full factorization over the reals, since those degree $2$ polynomials have no real roots.

(*) Even among teachers, unfortunately.

| cite | improve this answer | |
$\endgroup$
4
$\begingroup$

If everyone has ended up, as you say, with the factorization $x^6 - 64 = (x^2 - 4)(x^4 + 4x - 16)$, then everybody was wrong: if you take a look at only the free terms (i.e. the terms containing no $x$), you will see that they are $-64$ in the left-hand side, and $(-4)(-16) = +64$ in the right-hand side - which is impossible, therefore this factorization is not correct. The correct one is the one that you have produced. (The fact that your teacher had troubles with this one is a strong signal that you should move to another school - or even move to a country with a functional education system.)

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ I had been recreating the equations based on memory, and I believe that everyone had actually written "+ 16". Sorry about that, and thank you for your answer. $\endgroup$ – Evan Nov 16 '16 at 21:33
4
$\begingroup$

There are two errors in the factorization

$$x^6-64=(x^2-4)(x^4+4x-16)$$

The constant term in the quartic should be $+16$ instead of $-16$, and the linear term, $4x$, should be a quadratic term, $4x^2$. That is, the correct factorization is

$$x^6-64=(x^2-4)(x^4+4x^2+16)$$

This now agrees with the factorization $(x+2)(x^2-2x+4)(x-2)(x^2+2x+4)$ since $(x-2)(x+2)=x^2-4$ and

$$\begin{align} (x^2-2x+4)(x^2+2x+4)&=(x^2+4-2x)(x^2+4+2x)\\ &=(x^2+4)^2-(2x)^2\\ &=x^4+8x^2+16-4x^2\\ &=x^4+4x^2+16 \end{align}$$

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

A complete factorization of $x^6 - y^6$ can be performed as follows: $$\begin{align*} x^6 - y^6 &= (x^3)^2 - (y^3)^2 \\ &= (x^3 - y^3)(x^3 + y^3) \\ &= (x-y)(x^2 + xy + y^2)(x+y)(x^2 - xy + y^2). \end{align*}$$ The quadratic factors are irreducible in the ring of polynomials with rational coefficients $\mathbb Q[x]$ (more informally, they don't factor "nicely"). We can recombine these factors in carefully chosen ways to get expressions that might have resulted from an incomplete factorization; e.g., if we let $a = x^2 + y^2$ and $b = xy$, then $$\begin{align*} (x^2 + xy + y^2)(x^2 - xy + y^2) &= (a+b)(a-b) \\ &= a^2 - b^2 \\ &= (x^2+y^2)^2 - (xy)^2 \\ &= x^4 + 2x^2 y^2 + y^4 - x^2 y^2 \\ &= x^4 + x^2 y^2 + y^4. \end{align*}$$ And if we combine $(x-y)(x+y)$ we get $x^2 - y^2$; thus we recover the incomplete factorization of $x^6 - y^6$ as a difference of cubes $$(x^2)^3 - (y^2)^3 = (x^2 - y^2)(x^4 + x^2 y^2 + y^4).$$ There are of course other ways to combine these factors, each leading to a different expression, but all are algebraically equivalent.

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ The OP cannot perform some polynomial multiplications and you write that "The quadratic factors are irreducible in the ring of polynomials with rational coefficients $\Bbb Q[x]$"? Notice, too, that the OP isn't asking about how to factorize, but rather about why two factorizations are equivalent. $\endgroup$ – Alex M. Nov 16 '16 at 17:49
1
$\begingroup$

"How are $(x+2)(x^2−2x+4)(x−2)(x^2+2x+4)$ and $(x+2)(x−2)(x^4+4x^2+16)$ equivalent?"

Because $(x^2−2x+4)(x^2+2x+4)=x^4+4x^2+16$

===

Nother way of looking at it.

$a^3-b^3=(a-b)(a^2+ab+b^2) $

$a^2-b^2=(a-b)(a+b) $

So therefore $a^6-b^6=(a^2-b^2)(a^4+a^2b^2+b^4) =(a-b)(a+b) (a^4+a^2b^2+b^4)$

Yet, $a^6-b^6=(a^3-b^3)(a^3+b^3)=(a-b)(a^2+ab+b^2)(a^3+b^3) $

So it must be that $ (a+b) (a^4+a^2b^2+b^4)= (a^2+ab+b^2)(a^3+b^3) $ somehow.

So $(a+b)|(a^2+ab+b^2) $ or $(a+b)|(a^3+b^3) $.

$a^2+ab+b^2=a (a+b)+b^2$ which doesn't seem to work.

$a^3+b^3=a^2 (a+b)-a^2b+b^3=a^2(a+b)-ab (a+b)+ab^2+b^3=a^2 (a+b)-ab (a+b)+b^2 (a+b)-b^3+b^3=(a+b)(a^2-ab+b^2) $

So now we must have $ (a+b) (a^4+a^2b^2+b^4)= (a+b)(a^2+ab+b^2)(a^2-ab+b^2)$ and so it must be that:

$a^4+a^2b^2+b^4=(a^2+ab+b^2)(a^2-ab+b^2)$

And if we try to multiply it out, we see that it is so.

I don't blame the students for not seeing this, but the teacher ought to have recognize that it had to happen.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Now does this mean that (x^4 + 4x^2 + 16) isn't factored completely? if so, then I'm surprised, as my math teacher said that (x+2)(x−2)(x4+4x2+16) was factored completely. $\endgroup$ – Evan Nov 16 '16 at 21:45
  • $\begingroup$ I might have made a mistake but I don't think so and I'm a bit concerned you teacher didnvt catch this. $(x^2+4 -2×)(x^2+4+2x)=(x^2+4)^2 -4x^2=x^4+8x^2 ×16-4x^2=x^4+4x^2+16$. Yes it factors. $\endgroup$ – fleablood Nov 16 '16 at 22:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.